Expanding the Technology Acceptance Model (TAM) to Consider Teachers Needs and Concerns in the Design of Educational Technology (EdTAM) - Frøsig, Thomas B. (International Journal of Emerging Technologies in Learning (iJET), 2023)
While technological innovations are designed with the users in mind, this same design approach—designing technology to enhance the students’ learning experience—often falls short of acceptance with teachers and educators. This paper suggests a theoretical model with which EdTech can be designed to enhance the adoption of technology among teachers. At its core, the Educational Technology Acceptance Model (EdTAM) utilizes a double-user scenario, focusing on both the needs and concerns of teachers as well as the needs of students. As a result, a proof of concept in the form of an educational game designed in strict accordance with the EdTAM Model is presented. Thus showing that the theoretical model can be transferred into the design of a real-world product. A further study testing the effect of the model and the produced games acceptance rate with teachers is planned to support the theoretical model with empirical data.